The Prevalence and Severity of Acquired Blepharoptosis in US Eye Care Clinic Patients and Their Receptivity to Treatment - Matossian C (Clinical Ophthalmology, 2024)
Cynthia Matossian Matossian Eye Associates, Doylestown, PA, USACorrespondence: Cynthia Matossian, 3096 Comfort Road, New Hope, Doylestown, PA, 18938, USA, Tel +1 215-208-6944, Email cmatossianmd@icloud.comPurpose: To assess the presence and severity of acquired blepharoptosis (ptosis) among patients visiting an eye care clinic and the receptivity of eligible patients to pharmacologic treatment with oxymetazoline 0.1% ophthalmic solution.Patients and Methods: Patients aged 50 years or older who had a scheduled clinic appointment for any reason (eg, dry eye, cataract surgery consultation) were asked to respond to written questions about lid position and select whether their upper lid position most closely matched one of 4 images shown to them corresponding to no, mild, moderate, or severe ptosis. Patients selecting any of the mild, moderate, or severe ptosis were offered treatment with oxymetazoline 0.1% ophthalmic solution, barring any medical contraindications. The outcome measures were the proportion of patients with each self-reported lid position level (none to severe ptosis), the proportion of patients with asymmetric ptosis, and the proportion of patients willing to accept the treatment.Results: Data for 188 eyes of 94 patients were analyzed. Overall, 73.4% of patients had ptosis in at least one eye, and 25.5% had an asymmetric upper eyelid presentation. The proportions of patients with self-reported mild, moderate, or severe ptosis in at least one eye were 41.5%, 25.5%, and 6.4%, respectively. Among those patients eligible for treatment, 19.7% were willing to accept the treatment.Conclusion: Based on patients’ self-assessment of lid position, this study suggests a higher prevalence of ptosis than reported previously. Evaluation of the eyelids should be a standard part of the comprehensive eye examination.Keywords: blepharoptosis, ptosis, severity of ptosis, oxymetazoline ophthalmic solution, lid position